Sosialisasi Self-Efficacy dan Motivasi Belajar IPA Peserta Didik Kelas VIII di SMPN 2 Gerung Berdasarkan Gender - Via Monica Devi; Akhmad Badrul Ula (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Self-efficacy basically has a close relationship with students' learning motivation. Where between male and female students, of course, there are some differences in the level of self-efficacy and learning motivation. Therefore, it is necessary to make efforts to build self-efficacy and learning motivation of students, one of which is by carrying out socialization activities, especially in science learning. The method used consists of several steps, namely the stages of preparation, implementation, and evaluation. Based on the results obtained, the self-efficacy of male students was much higher than that of female students with an average score of 83% in the very high category. As for learning motivation, female students have a higher average than male students, where the average is ≥83% in the very high category. So it can be concluded that self-efficacy and learning motivation of students are interrelated, but have a slight difference if data collection is carried out based on gender.